I'm Ok - Kim, Patti, 1970- (Atheneum Books For Young Readers, 2018)
Ok, a Korean American boy, tries a get rich quick scheme of starting a hair braiding business and winning the school talent competition to hide the fact that he is struggling with the loss of his father and the financial hardships he and his mother must now bear.--